New Detection Method for Alkylphenol Traces in Water Based on an Integrated Electrochemical Cell Sensor - Chmayssem, Ayman; Hauchard, Didier (Revue des sciences de l’eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2015)
In order to evaluate the efficiency and to monitor the treatment of organic micropollution by advanced oxidation processes, we have developed a new detection method based on the use of an electrochemical sensor for alkylphenol detection in water. This sensor, integrating a three-electrode cell configuration, is a commercial screen-printed electrode (SPE-110GPH) that can be used for alkylphenol detection continuously by mean of a derived flow cell. The working electrode is modified by a graphene layer that enhances the sensor sensibility. The experimental conditions were optimized for the sensor incorporated into the flow cell. Linearity ranges, repeatability and accuracy were studied as well as the detection limits for each alkylphenol. The lowest detection limit was obtained with bisphenol A (60 nM) and the measurement ranges achievable with the SPE-110GPH electrode allow the continuous monitoring of treatment processes.